1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Elastic potential

  1. Nov 15, 2013 #1

    please just remind me

    if I have elastic potential U=( K(x-X0)^2 )/2 for the flexible spring moved on X distance from the initial X0 position So I have I have elastic force F=K(x0+vt-x) wich is the derivative of the U. Its not clear for me why vt term which should be equal to x in this equation is present ? From the general assumption (x-X0)^2 should be x^2-2*X*X0+X0^2 where is the vt term here?

  2. jcsd
  3. Nov 15, 2013 #2
    what's vt?

    looks like you differentiated incorrectly.
  4. Nov 15, 2013 #3
    x = V (velosity) * t (time)
    both of that formulas are from textbooks.

    Reasonable U= (Kx^2)/2 so force = kx. wehat fould be force if U=( K(x-X0)^2 )/2 in case when we moved body from the initial position (Xo) on X. The delta X should give us velosity should it?
  5. Nov 15, 2013 #4

    Philip Wood

    User Avatar
    Gold Member

    x = vt is for a body moving at constant velocity for a time t. I wouldn't have thought this was the case here. So we have simply

    [itex]U = \frac{1}{2}k(x - x_0)^2[/itex]

    [itex]F = -\frac{dU}{dx} = -k(x - x_0)[/itex] (having used chain rule)

    The minus sign in front of the k indicates that the force is in the -x direction.
  6. Nov 15, 2013 #5

    Some calculus:
    In the F=K(x0+vt-x) dealing with the constant velosity vt should be equal to 0, shouldnt it?

    In the chain rule we have f(x)= x-x0 and g(y)=y^2 so solving it we obtain that (x-xo)' should be 1. I dont understand why its not 0.

  7. Nov 15, 2013 #6

    Philip Wood

    User Avatar
    Gold Member

    Don't understand why you're bringing in vt, especially since you seem to have both x and vt in this equation. Stick with just x, unless you're sure that x really does vary with time as x = vt.

    [itex] \frac{d}{dx}\frac{1}{2}k(x - x_0)^2 = \frac{1}{2}\frac{d}{du}u^2 \frac {du}{dx}[/itex]

    in which [itex]u = (x - x_0)[/itex] so [itex] \frac{du}{dx} = 1[/itex]

    and [itex]\frac{d}{du}u^2 = 2u[/itex]

    So [itex] \frac{d}{dx}\frac{1}{2}k(x - x_0)^2 =k(x - x_0)[/itex].
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook